Implementasi Kartu Domino dalam Meningkatkan Keterampilan Berbicara - Alamsyah Alamsyah; Muftihaturrahmah Burhamzah; Suwarsih Bachtiar (Universitas Negeri Makassar, 2021)
Abstract. The purpose of this study was to determine the improvement of oral skills and academic achievement of German class XI IPA 1 SMAN 2 Makassar through domino cards. This research is a classroom action research. The direction of action is determined jointly by researchers, teachers, and students. The object of this research is the students of class XI IPA 1 SMAN 2 Makassar. The research was conducted in two cycles. Each cycle includes planning, implementing actions, observing and reflecting.Data collection techniques in the form of class observations, interviews, field notes, questionnaires, documents, and tests of German oral skills. Using qualitative descriptive data analysis. The results showed that: (1) The positive attitude of students in learning German oral skills increased by 16.56%, showing a polite, disciplined, caring, responsible, tolerant and positive attitude. (2) The increase in the oral German language skills of students of class XI IPA 1 SMAN 2 Makassar by 14.63% through Domino cards.